Early Transcriptome Response of Trichoderma virens to Colonization of Maize Roots - Taylor, James T.; Wang, Ken-Der; Horwitz, Benjamin; Kolomiets, Michael; Kenerley, Charles M. (Frontiers in Fungal Biology, 2021)
Trichoderma virens is a well-known mycoparasitic fungal symbiont that is valued for its biocontrol capabilities. T. virens initiates a symbiotic relationship with a plant host through the colonization of its roots. To achieve colonization, the fungus must communicate with the host and evade its innate defenses. In this study, we explored the genes involved with the host communication and colonization process through transcriptomic profiling of the wild-type fungus and selected deletion mutants as they colonized maize roots. Transcriptome profiles of the T. virens colonization of maize roots over time revealed that 24 hours post inoculation appeared to be a key time for plant-microbe communication, with many key gene categories, including signal transduction mechanisms and carbohydrate transport and metabolism, peaking in expression at this early colonization time point. The transcriptomic profiles of Sm1 and Sir1 deletion mutants in the presence of plants demonstrated that Sir1, rather than Sm1, appears to be the key regulator of the fungal response to maize, with 64% more unique differentially expressed genes compared to Sm1. Additionally, we developed a novel algorithm utilizing gene clustering and coexpression network analyses to select potential colonization-related gene targets for characterization. About 40% of the genes identified by the algorithm would have been missed using previous methods for selecting gene targets.